Uranium Isobaric Effect Correction for Determination of Pu-238 in Spent Nuclear Fuel by Thermal Ionization Mass Spectrometry - Jeon, Young-Shin; Park, Yang-Soon; Kim, Jung-Suk; Joon Park, Yong; Song, Kyuseok (Asian Journal of Chemistry, 2014)
The correction for 238U isobaric effect was investigated to determine the 238Pu isotope content. It is generally difficult to get rid of uranium effect on the measurement of 238Pu by mass spectrometry because plutonium cannot be purely separated from spent nuclear fuel and uranium exists on filament and in reagents as the impurities. The effect of 238U was corrected by measuring Pu+ and UO+ in the sample spiked with 233U and subtracting the uranium effect from the measured values. We controlled the heating currents of vaporization and ionization filaments to get the different ions of U+, Pu+, UO+ and PuO+ using thermal ionization mass spectrometry. For the Pu-U mixed solution, uranium was detected at lower filament temperature compared to plutonium, and the UO+ peak was larger than the U+ peak. The 238U/233U ratio was obtained by measuring the 238UO+/233UO+ ratio at low temperature in a mixed solution of plutonium and 233U (> 98 atom %) and then the 238Pu/239Pu ratio was obtained by measuring the (238Pu+238U)/239Pu and 233U/239Pu ratios at high temperature. For the plutonium standard solution, New Brunswick Laboratory-Certified Reference Material, Plutonium oxide (NBL CRM No. 122-PuO2), the 238Pu isotope composition obtained after 238U correction was approximately 15 % lower than the measured value before the correction. The 238Pu isotope composition after the 238U correction for the plutonium solution that separated from the spent nuclear fuel was 30 % lower than the measured value.